Pemberdayaan Kelompok Wanita Tani Melalui Inovasi Penanaman Tumpang Sari Berbasis Pertanian Berkelanjutan di Desa Wonopringgo Kabupaten Pekalongan - Farchan Mushaf Al Ramadhani; Heri Ariadi; Ahsarul Mufid; Ubad Badrudin; Fariz Kustiawan Alfarisy; Wagiyana Wagiyana; Elvin Cahyanita; Dimas Hari Sapto (Rahmah : Jurnal Pengabdian Masyarakat, 2026)
This community service program aimed to improve the knowledge of the Women Farmers Group (KWT) regarding an intercropping system based on sustainable agriculture in Wonopringgo Village, Pekalongan Regency. The problems faced by the community included limited understanding of intercropping cultivation techniques and the dominance of monoculture farming systems, resulting in suboptimal land utilization. The activity was conducted on September 1, 2025, at the Intercropping Demonstration Plot in Wonopringgo Village involving 25 KWT members. The implementation methods included investigation, preparation, action, extension and training, reflection through pre-tests and post-tests, and mentoring. The intercropping system applied combined maize and soybean plants. The results showed an increase in participants’ knowledge regarding the intercropping system and its benefits. During the pre-test, only 2 participants (8%) understood the intercropping system, while after the activity all participants (100%) understood it. Participants’ understanding of the benefits of intercropping also increased from 0% to 100% after the activity.